2017
DOI: 10.1016/j.humpath.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of atypical lipomatous tumor/well-differentiated liposarcoma and dedifferentiated liposarcoma: utility of p16 in combination with MDM2 and CDK4 immunohistochemistry

Abstract: The differential diagnosis between atypical lipomatous tumor/well-differentiated liposarcoma (ALT/WDLPS) and dedifferentiated liposarcoma (DDLPS) from their morphologic counterparts is challenging. Currently, the diagnosis is guided by MDM2 and CDK4 immunohistochemistry (IHC) and is confirmed by the amplification of the corresponding genes. Recently, p16 IHC has been proposed as a useful diagnostic biomarker. The objective was to assess the utility of p16 IHC in the differential diagnosis of ALT/WDLPS and DDLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 25 publications
4
66
0
Order By: Relevance
“…The use of immunohistochemistry (IHC) for MDM2 and CDK4 has been proposed as a more cost-effective solution for determining the diagnosis and is widely available, while FISH is typically only used at tertiary referral centers. However, for borderline cases, MDM2 FISH has been shown to be required for accurate pathologic diagnosis given the potential for sampling error on biopsy and subjective interpretation of MDM2 immunohistochemistry [ 8 , 15 ]. Meanwhile, MDM2 FISH has been shown to have 100% sensitivity and specificity even on core needle biopsy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of immunohistochemistry (IHC) for MDM2 and CDK4 has been proposed as a more cost-effective solution for determining the diagnosis and is widely available, while FISH is typically only used at tertiary referral centers. However, for borderline cases, MDM2 FISH has been shown to be required for accurate pathologic diagnosis given the potential for sampling error on biopsy and subjective interpretation of MDM2 immunohistochemistry [ 8 , 15 ]. Meanwhile, MDM2 FISH has been shown to have 100% sensitivity and specificity even on core needle biopsy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 As a potential downstream protein of EGR1, 6 p16, has been reported to be associated with malignancy and worse prognosis in multiple mesenchymal tumors. [7][8][9] We found that high p16 expression (defined as positivity ! 50% tumor cells) is significantly associated with malignancy (p ¼ 0.015) and shorter disease-free survival time (p ¼ 0.045) among all tumors (►Fig.…”
Section: Discussionmentioning
confidence: 96%
“…To help assess its tumoral nature, ancillary techniques such as MDM2/CDK4, HMGA2, or P16 immunohistochemistry can be helpful since all of these markers are frequently overexpressed in ALT/WDL/DL [1416]. More recently, it has been reported that diffuse and intense P16 staining is highly sensitive for ALT/WDL/DL, although P16 lacks specificity and needs to be combined with MDM2/CDK4 for an accurate diagnosis [17, 18]. FISH can also be performed to confirm the presence of MDM2 amplification, especially on surgical margin in doubtful cases.…”
Section: Discussionmentioning
confidence: 99%